1987
DOI: 10.1021/bk-1987-0350.ch017
|View full text |Cite
|
Sign up to set email alerts
|

N-Isopropylacrylamide and N-Acryloxysuccinimide Copolymer

Abstract: A copolymer capable of reaction with biologically active proteins was synthesized by a free radical polymerization in tetrahydrofuran (THF) under anhydrous conditions using azobisisobutyronitrile as the thermal initiator. Longer chain polymers were prepared using benzene instead of THF to avoid chain transfer. The thermally reversible phase transition properties of the copolymers suggested potential applications to the technologies of product isolation and pollutant removal. Conjugation of a monoclonal immunog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…Moreover, the photon correlation spectroscopy of Yamamoto, Iwasaki and Hirotsu (5) has indicated that collapse in the hydrodynamic radius occurs several degrees lower than that of phase separation. Finally, the research group of Hoffman has observed that modification of PNIPAAM can result in an inability to visually detect aggregation above the LCST at all due to the formation of submicron-size particles (22). Therefore, cloud point measurements for determination of the LCST suffer as a result of dependence on instrumental sensitivity to scattering.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the photon correlation spectroscopy of Yamamoto, Iwasaki and Hirotsu (5) has indicated that collapse in the hydrodynamic radius occurs several degrees lower than that of phase separation. Finally, the research group of Hoffman has observed that modification of PNIPAAM can result in an inability to visually detect aggregation above the LCST at all due to the formation of submicron-size particles (22). Therefore, cloud point measurements for determination of the LCST suffer as a result of dependence on instrumental sensitivity to scattering.…”
Section: Resultsmentioning
confidence: 99%
“…1.5 kcal/mol of repeating units, consistent with the loss of ca. 1 hy drogen bond per repeating unit upon phase separation (22). Studies of the endotherm associated with the LCST of this sample (at 0.4 mg/ml) show that the peak shape (transition width (ΔΤ1/2) = 0.4 ± 0.1°C, relative height (ACp) = 13 ± 1 cal/°C-g of poly mer) and maximum (LCST) are independent of heating rate over a range from 3.3 to 30°C/hr.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase separation on heating is believed as a phase behavior with the lower critical solution temperature (LCST) [3] which is common to all polymer solutions, although it is stilll controversial [4]. This phase transition of PNIPAM has been used in attempts to control the enzymatic activity [5][6][7][8][9], affinity precipitation separation [10,11] and protein recycling systems [12][13][14][15]. Another growing area in which this property has been exploited is a targeted delivery of drugs and chemical agents such as anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental Section) yields well-defined cloud points at least up to 5 mM SDS. The precipitated particles are apparently too small to cause visible turbidity at high surfactant concentrations (33). We can rationalize the retarded intermolecular aggregation as a consequence of the polymer-bound charged micelles leading to interparticle repulsion.…”
Section: Resultsmentioning
confidence: 88%